2022
DOI: 10.5194/acp-22-419-2022
|View full text |Cite
|
Sign up to set email alerts
|

Observed slump of sea land breeze in Brisbane under the effect of aerosols from remote transport during 2019 Australian mega fire events

Abstract: Abstract. The 2019 Australian mega fires were unprecedented considering their intensity and consistency. There has been much research on the environmental and ecological effects of these mega fires, most of which focused on the effect of huge aerosol loadings and the ecological devastation. Sea land breeze (SLB) is a regional thermodynamic circulation closely related to coastal pollution dispersion, yet few have looked into how it is influenced by different types of aerosols transported from either nearby or r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Some months in spring and autumn have similar amount of SWR as those in summer since the in situ SWR is influenced by both solar zenith angle and cloud. Except for high aerosol emission periods, lower cloud cover offsets the effect of smaller solar zenith angle through weaker “Umbrella Effect” to ensure enough in situ SWR, which boosts the triggering of SLB (Miller et al., 2003; Shen, Zhao, Yang, Yang, & Zhou, 2022; Shen et al., 2021a). Most importantly, not all SLB days have higher level of SWR flux than the monthly mean SWR flux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some months in spring and autumn have similar amount of SWR as those in summer since the in situ SWR is influenced by both solar zenith angle and cloud. Except for high aerosol emission periods, lower cloud cover offsets the effect of smaller solar zenith angle through weaker “Umbrella Effect” to ensure enough in situ SWR, which boosts the triggering of SLB (Miller et al., 2003; Shen, Zhao, Yang, Yang, & Zhou, 2022; Shen et al., 2021a). Most importantly, not all SLB days have higher level of SWR flux than the monthly mean SWR flux.…”
Section: Resultsmentioning
confidence: 99%
“…Third, only local wind signals during PTS (PTL) on SLB days are selected to further calculate the average SLB speed. With the help of these 3 filters, the reliability of this method has been proved from several perspectives, including the comparison between its outcome and objective climate (physical process) analysis (Shen, Zhao, & Yang, 2022; Shen, Zhao, Yang, Yang, & Zhou, 2022; Shen et al., 2021a). In order to make it clear, we further introduce briefly with critical points in these three steps being clarified.…”
Section: Methodsmentioning
confidence: 99%
“…(2019) demonstrated that the monthly average SLBD during the summer of Shanghai from 2003 to 2010 was 5, that is, 7 days less than that during the summer in Tianjin over the same period. Only 4 SLBD in January 2020 in Brisbane were observed (Shen et al., 2022), that is, 5 days less compared to Tianjin. In Cotonou, where the West African monsoon is prevalent, a total of 417 SLBD were observed over the five years from 2006 to 2010 (Gbambie & Steyn, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The number of SLBD fluctuated at post-2011 after a sharp decline was observed before 2011. Only 4 SLBD in January 2020 in Brisbane were observed (Shen et al, 2022), that is, 5 days less compared to Tianjin. In Cotonou, where the West African monsoon is prevalent, a total of 417 SLBD were observed over the five years from 2006 to 2010 (Gbambie & Steyn, 2013).…”
Section: Observed Long-term Variations In the Characteristics Of Slbmentioning
confidence: 89%
See 1 more Smart Citation